The Technological Integration of Big Data and the Body: A Phenomenological Analysis of the Evolution of Clinical Cognitive Paradigms - Lihui WANG (Yixue yu zhexue, 2025)
The integration of technology and the body is increasingly blurring the boundaries between the natural and the artificial, raising significant ethical and privacy concerns. In this context, interdisciplinary research in clinical phenomenology is of particular importance. It focuses on individual direct experiences and historical contexts, offering a critical and practical approach to understanding the impact of technology on life. By emphasizing bodily perception, desire, and historicity, it provides a foundation for interdisciplinary dialogue to address the ethical challenges posed by technological advancements. Through this approach, we can gain a more comprehensive understanding of how data technologies shape the life world and ensure the moral and equitable application of technology while respecting the diversity of life.